A macroscopic strain-space model of anisotropic, cyclic plasticity with hardening. (December 2018) - Paranjape, Harshad M.; Stebner, Aaron P.; Bhattacharya, Kaushik
Highlights: We present a macroscopic, strain-based formulation for cyclic plasticity. The formulation incorporates both isotropic and kinematic hardening. The initial yielding and subsequent kinematic hardening account for anisotropy. The model is demonstrated to capture ratcheting response on cyclic loading, anisotropy in initial yield in rolled sheet metal, and anisotropic hardening. Graphical abstract: Abstract: We present a strain-based formulation of macroscopic plastic deformation that accounts for anisotropy in both the initial yielding and subsequent hardening. Both isotropic and kinematic hardening are considered. Thus the model captures the evolution in the deformation response on cyclic loading including the Bauschinger effect, and the accumulation of plastic strain (ratcheting response). The model is formulated in the strain space and implemented using an implicit time integration scheme. The capabilities of the model are demonstrated through material parameter studies and by calibrating the model to experimental data for uniaxial tensile loading of Inconel alloy and anisotropic yielding of rolled aluminum alloy sheets. We also show that this strain-based approach is equivalent to the more traditional stress-based approach. The strain-based formulation of this model makes it attractive for coupling with other strain-based phenomena like phase-transformations in shape-memory alloys and failure.